Pengaruh L-Karnitin terhadap Kadar Lemak Daging dan Komposisi Tubuh Ikan Patin (Pangasius hypopthalmus) - Suwarsito Suwarsito (Universitas Gadjah Mada, 2007)
This study was conducted to investigate the effect of dietary L-carnitine level on muscular lipid and body composition of asian catfish (Pangasius hypopthalmus). Four isoprotein and isocaloric diets with different levels of L-carnitine, 0.00% (diet K), 0.10% (diet A), 0.18% (diet B), and 0.29% (diet C) were applied in this experiment. Ten fishes with initial body weight of 35.86 ± 1.54 g were cultivated in each aquarium (water volume 60 l) for 50 days. Fishes were fed three times daily at satiation. The results showed that L-carnitine in the liver increased by increasing dietary L-carnitine level. While increasing dietary L-carnitine until 0.18% decreased content of lipid in the liver, but excessive dose of dietary L-carnitine increased content of lipid in the liver. It was further observed that L-carnitine in the diets reduced the muscular lipid content from 32.35 to 7.51% dry weight, but had no effect on body composition.